Role of Ubiquitin-Specific Peptidase 47 in Cancers and Other Diseases - Pan, Kailing; Fu, Junhao; Xu, Wenxia (Frontiers in Cell and Developmental Biology, 2021)
Deubiquitination is the reverse process of ubiquitination, which is catalyzed by deubiquitinase enzymes. More than 100 deubiquitinases have been identified. USP47, a member of the ubiquitin-specific protease family with high homology to USP7, is an active molecule with a wide range of functions and is closely associated with cancer and other diseases. However, no systematic summary exists regarding the functions of USP47. Here, we summarize the functions and expression regulation of USP47. USP47 is highly expressed in many tumors and is widely involved in tumor development, metastasis, drug resistance, epithelial-mesenchymal transition, and other processes. Targeted inhibition of USP47 can reverse malignant tumor behavior. USP47 also plays a role in inflammatory responses, myocardial infarction, and neuronal development. USP47 is involved in multiple levels of expression-regulating mechanisms, including transcriptional, post-transcriptional, and post-translational modifications. Development of targeted inhibitors against USP47 will provide a basis for studying the mechanisms of USP47 and developing therapeutic strategies for cancers and other diseases.